DETERMINANTS AND PREFERENCES FOR MARKETABILITY OF FIRMS SHARES FOR INVESTORS: A CAUSAL STUDY OF PAKISTAN’S FERTILIZER SECTOR (Singaporean Journal of Business Economics and Management, 2016)
Pakistan is basically an agricultural country. Main components of its GDP are directly and indirectly linked with the agriculture products. In order to increase the growth of agricultural products, fertilizer products including Urea and Pesticides are very important. The fertilizer industry is also considered as most flourishing industry in Pakistan in recent era having huge abnormal profits and best return. Our study have basically analyzed the financial performance of that sectors to provide some key indicators to the investors that will help them to make sure that their investments are going in the right directions. Four major Pakistan Stock Exchange listed companies for data analysis and the results shows that the profitability is the main cause that will help these companies to increase their marketability from investor's point of view. Also in profitability it is the Net Profit Margin (NPM) and Return on Equity (ROE) that play a vital role in enhancing the marketability of the company's share in the market.